Stock Prices Affected by Good Corporate Governance and Financial Performance - Fayanni, Yenni; Soetedjo, Soegeng (Opción, 1970)
In this study, the authors propose to evaluate the application ofGood Corporate Governance and Financial Performance to the stockprices of manufacturing companies listed on the Indonesia StockExchange. The research method used is descriptive method with aquantitative approach. In this statement, the population used in thisstudy is the financial statements of manufacturing companies listed onthe Indonesian stock exchange from 2016 to 2018, the technique ofdetermining the sampling uses Purposive Sampling. This research datauses secondary data, financial statements of manufacturing companieslisted on the Indonesia stock exchange from 2016 to 2018. All datasources were obtained from the website of the Indonesia StockExchange at https://www.idx.co. ID, company website as well asGoogle search. Our analysis reveals that Independent Commissionersand Managerial Ownership, PBV and NPM affect stock prices, whilefor Institutional Ownership does not affect stock prices. The value ofimplementing Good Corporate Governance and Financial Performanceon the price of manufacturing companies listed on the Indonesia StockExchange is 64.5%, while 35.4% is explained by other factors whichare not included in this study.